EKO-SPIRITUALITAS DALAM PEMIKIRAN SAYED HUSEIN NASHR - Satria, Adam; Sholihul Huda (Al Hikmah, 2024)
The environmental crisis in the modern era is currently a very serious issue. Environmental crises, such as deforestation, extinction of wildlife, plastic waste pollution, environmentally unfriendly industrialization activities, illegal logging and forest fires are prime examples. Various solutions have been offered from various perspectives, but this research discusses and offers solutions from the perspective of Islamic teachings by its originator, namely Sayed Husein Nashr. The aim of this research is to find out the answer to Islamic teachings to the challenges of the environmental crisis, to know the responsibility of humans as balancers of nature, and to understand how important education and spiritual awareness are in successfully preserving a sustainable environment. This research uses a qualitative method with a content analysis approach. Sayed Husein Nashr from an Islamic perspective stated that a more fundamental spiritual crisis is a manifestation of the environmental crisis we are currently facing. Holistic education and increasing spiritual awareness can be a solution to this problem.